Error propagation in the Abel hill inverse problem - Kincanon, Eric (International Journal of Applied Mathematical Research, 2023)
Abel’s Hill considers the problem of how to determine the shape of the hill from information on the return time of a rolled ball. Though this problem has been solved for piecewise monotonic functions, the issue of error propagation has not been addressed. This paper considers how errors in time measurement correlate to errors in determining the shape of the hill.